Caregivers' use of robots and their effect on work environment – a scoping review. Issue 3 (3rd July 2022) - Persson, Marcus; Redmalm, David; Iversen, Clara
Abstract: Despite the lively discussion on the pros and cons of using robots in health care, little is still known about how caregivers are affected when robots are introduced in their work environment. The present scoping review fills this research gap by mapping previous studies about the relation between robots in care and caregivers' working life. The paper is based on searches in four databases for peer-reviewed articles about robots in care settings, published 2000 to 2020. The 27 included papers were examined with the questions of 1) how robots are used by caregivers, and 2) how robots affect caregivers' work environment. The analysis shows that the use of robots can affect both the physical and the psychosocial work environment, in positive as well as in negative ways. Robots are used in care settings to reduce physical and mental demands of the caregivers, but they can, in fact, increase caregivers' workload. Thus, the review indicates that robots can improve the quality of work, but that they seldom work as a shortcut to increased efficiency or time effectiveness.